Assessments of midwives’ knowledge and practice toward postpartum hemorrhage management and associated factors at selected public hospitals in Addis Ababa, Ethiopia, 2023AJOG Global Reports at a Glance - Ashenu Bidiru, MSc; Heyria Hussein, MSc; Tola Getachew Bekele, MSc; Tilahun Teshager, MSc; Fenta Wondimneh, MSc; Indeshaw Ketema, MSc; Beyene Feleke, MSc; Lema Daba, MSc; Merga Shelema, MSc (AJOG Global Reports, 2025)
BACKGROUND: Postpartum hemorrhage as the primary cause was associated with 41% to 51% of all maternal deaths in Ethiopia between 2013 and 2018. The majority of postpartum hemorrhage–related deaths can be avoided by using efficient therapies and having midwives with good knowledge and skills. OBJECTIVE: This study aimed at determining the knowledge and practices of midwives related to postpartum hemorrhage management and associated factors at selected public hospitals in Addis Ababa, Ethiopia. STUDY DESIGN: An institutional-based, cross-sectional study design was employed from March 15 to April 15, 2023. A simple random sampling technique was used to select the 207 sampled participants. Data were collected using a pretested, structured, self-administered questionnaire. Data coding and cleaning were done before data analysis. Variables with a P value <.25 in the bivariate logistic regression analysis were entered and checked for association in a multivariable logistic regression model so as to not miss an important variable. The finding was expressed as the adjusted odd ratio with 95% confidence interval and a variable at a P value of <.05 was declared as statistically significant. RESULTS: In this study, 34.3% (95% confidence interval, 28–41) of the study participants had good knowledge, whereas 65.7% (95% confidence interval, 59–72) had poor knowledge. Participants who had received job training in the labor ward had 3 times better knowledge than those who did not receive it (adjusted odds ratio, 3.386; 95% confidence interval, 1.427–8.033). In total, 30.4% (95% confidence interval, 24.6–37.6) of the participants had good practice, whereas 69.6% (95% confidence interval, 62.4–75.4) had poor practice. CONCLUSION: The participant responses showed that the majority of midwives lacked adequate knowledge of and practice related to postpartum hemorrhage management. All stakeholders should consider on-job training for participants, improving educational levels, and continuous screening and identification of institutional needs.